Análise de tipos e concentrações de inóculos para potencializar a geração de biogás na digestão anaeróbia da fração orgânica dos resíduos sólidos domiciliares (FORSD) do Bairro Pici, Fortaleza – CE - Lima, Naiane Costa (2015)
Considering the importance of anaerobic digestion for reuse the organic fraction of solid waste and the possibility of power generation through the biogas produced, the research aims to find ways to optimize the process digestion, by testing with different inoculants and relationships Food / Micro-organisms. The experiment consisted of the analysis and evaluation of different inoculants and relationships Food / Microorganisms (A / M) in order to optimize the anaerobic digestion of organic solid waste, which were collected in homes near Federal University of Ceará - Campus do Pici. In first phase of the research, the physical and chemical properties were characterized Four different inoculants. In the second phase, the activity test was performed specific methanogenic. After evaluating the performance of inocula were selected two inoculants and proposed two ratios A / F, for the development of biodegradability test. There was also the physical and chemical characterization of substrate used for the formation of reactions means to the test biodegradability. During the biodegradability test media were characterized reactions before and after the test. In assessing the methanogenic activity of the four tested inoculum, the inoculum derived from the sewage treatment plant of a beer industry (inoculum 3) presented the highest performance with AME maximum of 0.80 gCOD / GSV · d, maximum volume of methane 21.98 mL and 67.5% of methane present in biogas, even in a shorter period of 0.83 days vs. with other samples. Assessing the methanogenic activity and the production of biogas in biodegradability test inoculum 3 with a ratio A / F made a 0.5 best performance, with a maximum volume of methane 29.31 mL, one AME maximum of 0.47 gCOD / GSV · 58.5% of methane present in biogas, in a period short of 3.81 days. It was concluded that an inoculum with similar characteristics to inoculum 3 are more suitable for anaerobic digestion of the organic fraction of solid waste.